PERPUSTAKAAN SEBAGAI RUANG HETEROTOPIA: TINJAUAN LITERATUR SISTEMATIS (SLR) - Yeni Fitria Nurahman (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
Research on libraries as heterotopian spaces has received growing scholarly attention, highlighting their role not only as repositories of information but also as complex symbolic, social, and experiential spaces. However, several gaps remain regarding how heterotopia is manifested in different types and forms of library spaces. This study aims to identify and analyze the characteristics of libraries as heterotopian spaces through a systematic literature review, focusing on spatial meanings, social functions, and ideological representations within library environments. This study employed a qualitative Systematic Literature Review (SLR) design. The findings show that both public and academic libraries exhibit heterotopian characteristics through their physical and digital spaces, symbolic functions, and sociocultural values. Significant differences were identified in how different library types construct cultural, educational, and ideological narratives through spatial design and user experience. These findings suggest that the heterotopia framework offers a critical lens for understanding the transformative role of libraries in the digital age. Future research is encouraged to explore additional library types and adopt interdisciplinary perspectives.